Analysis of Institutional Ownership, Audit Committee, Investment Opportunity Set, on Accounting Conservatism with Capital Intensity as Variable Moderation - Frengki Kurniawan (Politeknik Siber Cerdika Internasional, 2024)
This study aims to examine institutional ownership, audit committees, and investment opportunity sets on accounting conservatism which is moderated by capital intensity. The purposive sampling method was used as a method in collecting research data and the multiple regression equation model was used as a statistical analysis tool with the SPSS 25 application. The sample in this study were 23 issuers on the Indonesia Stock Exchange, especially manufacturing sector companies whose financial reports had been published for 4 (four) years. four) years from 2018 to 2021. Based on the results of this study, it shows that audit quality, capital intensity, institutional ownership, audit quality capital intensity, capital intensity, investment opportunity set have an effect on accounting conservatism. Meanwhile, institutional ownership and investment opportunity set have no effect on accounting conservatism.